ORGANIZATIONAL JUSTICE ON WORK OUTCOMES (Equilibrium: Jurnal Ekonomi Syariah, 2013)
The purpose of this study is to investigate the effect of organizational justice on work outcomes. The work outcomes can be viewed from organizational commitment, job satisfaction and employees’ turnover intention in Islamic microfinance institutions in Central Java, Indonesia. This study used three dimensions of organizational justice namely distributive, procedural, and interactional justice. Using self-administrated questionnaire 370 employees from 60 Islamic microfinance institutions were surveyed in order to test nine hypothesis of this study. SEM analysis of data indicates that distributive, procedural and interactional justice have positively significant effect on organizational commitment and job satisfaction. All three dimensions of justice also had negative significant impacted on employees’ turnover intention. Implication, limitation and suggestion for future research are discussed. Keywords: Distributive, procedural, and interactional justice, organizational commitment, job satisfaction, turnover intention and Islamic microfinance.